Using Learning and Motivation Theories to Coherently Link Formative Assessment, Grading Practices, and Large‐Scale Assessment - Shepard, L. A.; Penuel, W. R.; Pellegrino, J. W. (Educational measurement, issues and practice, 2018)
To support equitable and ambitious teaching practices, classroom assessment design must be grounded in a research‐based theory of learning. Compared to other theories, sociocultural theory offers a more powerful, integrative account of how motivational aspects of learning—such as self‐regulation, self‐efficacy, sense of belonging, and identity—are completely entwined with cognitive development. Instead of centering assessment within systems that support use of interim and end‐of‐year standardized tests, we argue for a vision of formative assessment based on discipline‐specific tasks and questions that can provide qualitative insights about student experience and thinking, including their identification with disciplinary practices. At the same time, to be consistent with a productive formative assessment culture, grading policies should avoid using points and grades “to motivate” students but should create opportunities for students to use feedback to improve their work. We argue for districts as the locus for the design of such coherent curriculum, instruction, and assessment activity systems because districts have responsibility for curriculum, teacher professional development, and equity; and districts allocate resources for textbooks and assessment.